The Middle Javanese passive prefix "ing-" - Kriswanto, Agung; Puspitorini, Dwi; Pudjiastuti, Titik (Wacana, Journal of the Humanities of Indonesia, 2025)
Evidence from literary texts originating from the Mount Merapi-Merbabu milieu in Central Java demonstrates the existence of a variant of the passive marker -in- affix, which has been in use since the early period of Old Javanese: the passive prefix ing-. The six literary texts that serve as the sources for this study indicate that the ing- prefix began to emerge during the fifteenth and sixteenth centuries, coinciding with the development of Middle Javanese. Previous researchers have not paid much attention to the ing- prefix, as it was considered merely incidental, especially since ing- was also found in texts from periods before the fifteenth century. Alongside the emergence of ing-, another form ring- appears, which serves the same grammatical function. This article focuses on two key issues: (i) ing- as a passive marker and (ii) passive construction patterns. The findings of this study reveal both similarities and differences in the grammatical characteristics of Javanese as used in texts from Merapi-Merbabu, compared to Old Javanese and Modern Javanese. The similarity between Middle Javanese and Old Javanese lies in passive constructions where the agent is expressed through suffixes for second- and third-person pronouns. Meanwhile, Middle Javanese and Modern Javanese share a similarity in passive constructions where the agent appears as a prefix for first- and second-person pronouns. The resemblance of Middle Javanese’s passive constructions to both Old Javanese and Modern Javanese within literary texts from the Merapi-Merbabu milieu suggests that this region preserves a transitional form of the language between Old Javanese and Modern Javanese.